2018
DOI: 10.3389/fnins.2018.00897
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Convulsing Dose Administration of Pilocarpine Reduces Glycemia, Increases Anxiety-Like Behavior and Decelerates Cortical Spreading Depression in Rats Suckled on Various Litter Sizes

Abstract: Epilepsy and malnutrition constitute two worldwide health problems affecting behavior and brain function. The cholinergic agonist pilocarpine (300–380 mg/kg; single administration) reproduces the human type of temporal lobe epilepsy in rats. Pilocarpine-induced epilepsy in rodents has been associated with glycemia, learning and memory and anxiety disturbances. Cortical spreading depression (CSD) is a neural response that has been linked to brain excitability disorders and its diseases, and has been shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
3
6
0
Order By: Relevance
“…The previously described in vivo CSD-induced ECoG potentiation (Lopes-de-Morais et al, 2014; Mendes-da-Silva et al, 2018) has been confirmed in this paper, and its modulation by pilocarpine and taurine has been described (Table 1). Data on anxiety-like behavior, MDA measurements and brain immunohistochemical effects that were produced by taurine and/or pilocarpine treatment represent novel evidence of the action of these compounds on 35–55-day-old rats, whereas data on weight gain, glycemia, and CSD confirm the results of a previous study (Francisco and Guedes, 2018). The stress that is associated with drug administration cannot be the cause of the reported alterations because – as first mentioned in the results section – the groups that received gavage and intraperitoneal injection of vehicle (saline and scopolamine) presented values similar to the naïve controls that received no gavage or intraperitoneal injection.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The previously described in vivo CSD-induced ECoG potentiation (Lopes-de-Morais et al, 2014; Mendes-da-Silva et al, 2018) has been confirmed in this paper, and its modulation by pilocarpine and taurine has been described (Table 1). Data on anxiety-like behavior, MDA measurements and brain immunohistochemical effects that were produced by taurine and/or pilocarpine treatment represent novel evidence of the action of these compounds on 35–55-day-old rats, whereas data on weight gain, glycemia, and CSD confirm the results of a previous study (Francisco and Guedes, 2018). The stress that is associated with drug administration cannot be the cause of the reported alterations because – as first mentioned in the results section – the groups that received gavage and intraperitoneal injection of vehicle (saline and scopolamine) presented values similar to the naïve controls that received no gavage or intraperitoneal injection.…”
Section: Discussionsupporting
confidence: 78%
“…Under this condition, no behavioral or electrocorticographic changes indicative of seizures were observed (Guedes and Vasconcelos, 2008). However, under subconvulsing paradigms several reports have described anxiety-like behavioral profiles (Duarte et al, 2014; Francisco and Guedes, 2018), reductions in glycemia (Francisco and Guedes, 2018), increases in brain oxidative stress (Mendes-da-Silva et al, 2018) and impairment of propagation of the excitability-related phenomenon known as cortical spreading depression (CSD) along the cortical rodent tissue (Francisco and Guedes, 2018; Mendes-da-Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, MeOH extracts revealed a more selective enzyme inhibition on AChE (Table 4). Recently, pilocarpine, a muscarinic receptor agonist, was able to antagonize CSD effects, after sub-convulsing dose administration [46], thus suggesting a role played by acetylcholine signaling stimulation, in CSD. Actually, extract capacity to improve 5-HT and acetylcholine pathways could be related to their antiradical activity (Table 3) [47].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, CSD was inhibited in chronic epileptic rats generated by status epilepticus induced with systemic injections of pilocarpine, effect that was reverted by increasing GABA-A activity with diazepam (Guedes and Cavalheiro, 1997), and treatment with sub-convulsive doses of pilocarpine reduced CSD propagation velocity in anesthetized naïve rats (Francisco and Guedes, 2018). Similarly, it has been shown that CSD does not penetrate into penicillingenerated cortical epileptic foci or electrically stimulated (6-10Hz) cortical areas of anesthetized rats (Koroleva and Bures, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…shown that blood infusion of carbachol can induce dilation of cephalic arteries and subsequent headache, but not migraine attacks (Schytz et al, 2010;Schytz et al, 2009). Notably, it has been shown that the non-specific muscarinic agonist pilocarpine at subconvulsive doses can decelerate CSD in anesthetized rats (Francisco and Guedes, 2018). However, the effect of central cholinergic modulation on migraine pathological mechanisms and its use in therapeutic interventions against spreading depolarizations has not been thoroughly investigated (Klass et al, 2018).…”
Section: Introductionmentioning
confidence: 99%